PENGARUH JOB TRAINING DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT AGRO NUSANTARA INDONESIA - Najiah, Neng Siti; Agung, Syahrum (PT Naureen Digital Education, 2024)
PT Agro Nusantara Indonesia has experienced fluctuations in fertilizer production over the past five years. This has been identified as being due to a lack of employee training and motivation. Job training is important for improving employee skills and can help companies optimize their investments. Motivated employees tend to be more enthusiastic and proactive in achieving company goals. This study used a quantitative method with a survey approach. Data were collected through questionnaires distributed to 52 PT Agro Nusantara Indonesia employees. A saturated sample was used, where the sample size equals the population size. The data analysis techniques used were t-tests and multiple linear regression. The results of the study show that: Job training does not have a significant effect on employee performance, Work motivation has a significant effect on employee performance, and Job training and work motivation have a simultaneous considerable effect on employee performance. The company needs to improve its work motivation programs to improve employee performance.